Added value of pre-procedural magnetic resonance angiography in transarterial embolization for refractory musculoskeletal pain - Pan, Chiao-Yun; Liang, Keng-Wei; Chen, Ting-Rong; Wang, Chien-Kuo; Liao, Wen-Ying; Lu, Ying-Hung; Hsiung, Yi-Cheng; Liu, Yi-Sheng; Wang, Bow (Frontiers in Medicine, 2024)
Transarterial microembolization (TAME) is a minimally invasive treatment for chronic musculoskeletal disorders. Identifying angiogenesis and the supplying vessels of the target joint is important but challenging. Although magnetic resonance imaging (MRI) is commonly used to diagnose musculoskeletal diseases, it typically excludes vascular imaging. Dynamic contrastenhanced magnetic resonance angiography (DCE-MRA) has the ability to visualize lesion angiogenesis, identify supplying vessels, and evaluate the vasculature anatomy. We propose that incorporating DCE-MRA into pre-procedural assessments can help identify the culprit vessels, arterial anatomy, and variant assessment of the target joint before TAME.We investigated six cases, each presenting pain in different body parts: shoulder adhesive capsulitis, trapezius myalgia, combined tennis and golf elbow, knee osteoarthritis, refractory knee pain after osteotomy, and plantar fasciitis. All patients underwent MRI with DCE-MRA before undergoing TAME. DCE-MRA was performed using either 1.5T or 3T MRI scanners, employing 3D-TRICKS or 4D-TRAK XD techniques. The numerical rating scale for pain was evaluated at one, three, and six months after the procedure, and any adverse events were recorded over the entire six-month followup period.Pre-procedural DCE-MRA helped to visualize angiogenesis at the lesion site in all patients and identify the supplying vessels, arterial vasculature anatomy, and branching variants. These findings corroborated the subsequent digital subtraction angiography (DSA) findings obtained during TAME. All patients experienced pain reduction and functional improvement after TAME without any complications. The average pain score reduced significantly after TAME treatment (P < 0.05). Two patients underwent a second MRI and DCE-MRA at the six-month follow-up and showed a significant reduction in angiogenesis.DCE-MRA offers a valuable pre-procedural assessment tool for TAME procedures by facilitating the visualization of angiogenesis at the lesion site, supplying vessels, and arterial anatomic variants, including the variable orifice of the supplying branches. This information can potentially improve patient selection and pre-procedural planning, leading to better outcomes and reduced risk of complications.